Gender-based discrimination in the nonprofit sector. Are nonprofit organizations hypocritical? - Bebjak, Pavol; Houdek, Petr, 1981-; Vranka, Marek, 1988-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
This thesis explored gender-based discrimination in the Czech Republic. It compares levels of unequal treatment across for-profit and nonprofit sectors using the methodology of a correspondence study. An experimental design with fictitious resumes (N = 170) was implemented to detect gender discrimination at junior-level positions. The analysis of the response rate across both sectors indicated that there is no presence of unequal treatment targeted towards any gender. Contrary to expectations based on some previous studies, nonprofits do not act hypocritically as no discriminatory behavior was detected.
Vedoucí práce: Petr Houdek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses